Mineralization of 15n-labelled legume residues in soils with different nitrogen contents and its uptake by rhodes grass - Yaacob, Othman; Blair, Graeme J. (Springer, 1980)
Soil was collected from pots that had grown I, 3 or 6 soybean (Glycine max) or Siratro (Macropullium atropurpureum) crops that had received organic residue returns from each crop. 15 N-labelled residues were added to half the pots in the experiment and the other half left unamended. Half of each group was then sown to Rhodes grass (Chloris gayana) which was grown, under glasshouse conditions, for 12 weeks. Ten grams of organic matter residues were added to each pot (1.5 kg soil) and the pots subjected to two wetting and drying cycles. At the end of the second wet cycle, soil mineral N values ranged from 6 to 64 ppm in unamended soils and from 19 to 177 ppm in amended soils. These levels generally declined over a 12 week period both in the presence and absence of sown grass. Nitrogen uptake by the grass increased with the number of previous cycles and was higher in Siratro than soybean soils. Recovery of 15 N by plant growth from the incorporated soybean residues was little effected by previous crop history and averaged 15.4%. On the other hand, Siratro recoveries were 13.7, 42.4 and 55.5% from soils that had grown 1, 3 and 6 previous Siratro crops, respectively. The addition of organic residues stimulated the release of native organic N (positive priming effect) on all soils. These results show that the turnover rate of nitrogen from organic residues can be high and the net result of these additions depends on the nature of the organic residues and the soil system to which they are added. These data emphasise the need to consider the rate of nutrient turnover from organic sources rather than concentrate on the nature and size of the resident nutrient pools.